United Kingdom : 2008 Article IV Consultation; Staff Supplement; Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for the United Kingdom. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
This 2008 Article IV Consultation highlights that the United Kingdom's economic growth was above trend in 2006 and 2007. In terms of expenditure, the expansion was largely driven by private consumption, on the heels of strong employment, steady real wage and living standards growth, and a surge in immigration. So far in 2008, evidence points to a sharp slowing in activity alongside high inflation. Executive Directors have welcomed the commitment made in the 2008 budget to tighten fiscal policy in the coming two years.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet